(3bGfhf GdJLGQI GdHMQjI aj VhA Gdabg hGdbVGAs - (3YHO GdMejO(B, (3GdefTGhjs ((3GdEScfOQjI(B:s (3efTCI GdeYGQa(B,s, 2005)
(3bGfhf GdJLGQI GdHMQjI(B- (3GdGMcGe GdYGeI(B- (3GdMbhb GdYjfjI Ydi GdSajfI(B- (3GdMLR Ydi GdSajfI(B- (3aj CTNGU GdedGMI GdHMQjI(B- (3GdhcdGA GdHMQjhf hGdebGhdhf GdHMQjhf(B- (3YbO Gdfbd GdHMQj(B- (3CMcGe NGUI HHYV CfhGY GdJCejf GdHMQj(B.s
(3GdeQGLY (B452 (3U(B.s
Keywords: (3GdJLGQI GdHMQjIs; (3GdbGfhf GdHMQjs; (3GdbGfhf GdLfGFjs; (3bGfhf GdJLGQIs